Protestant missionaries in Spain, 1869-1936: "shall the papists prevail?" - Eaton, Kent (Lexington Books, 2015)
The Protestant preoccupation with Spain -- The fellowship of dissent -- The development of dispensational missiology -- The awakening of Protestant interest in Spain as a mission field -- The first republic and the Protestant experience -- Spain and religious freedom, 1868-1875 -- Missionary methodology in Spain -- A precarious foundation -- Uncertainty and advances, 1875-1898 -- From darkness to light, 1898-1933 -- The calm before the storm -- The Protestant experience during the Second Spanish Republic -- The lasting legacy